How The Project Based Learning Implemented In “Kurikulum Merdeka”: A Case Study - Maryatun, Ika Budi; Salsabila, Faraumaina Sulihang Yangesti (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
This study aimed to describe project-based learning implementation in the “Kurikulum Merdeka” at TK Aisyiyah Nyai Ahmad Dahlan. This study used a qualitative approach and a case study type of research. The study subjects were the principal, curriculum team, class B teachers, and class group B4. Data collection techniques used interview techniques, observation, and documentation. Primary data sources comprised the principal, curriculum section, teachers, implementation of project learning, and their documents. The data analysis technique used the Miles and Huberman interactive analysis model. The data from the research results were re-tested for validity using triangulation techniques and sources. The study results showed that TK Aisyiyah Nyai Ahmad Dahlan implemented project-based learning in the “Kurikulum Merdeka”, which included the preparation, implementation, and assessment processes supported by factors of facilities, learning media, and activity actors. Meanwhile, project-based learning at TK Aisyiyah Nyai Ahmad Dahlan also experienced several obstacles, such as limited literature and references, differing perceptions between teachers regarding “Kurikulum Merdeka” learning, and loose part learning less varied media